Implementasi Program Pencegahan dan Penanggulangan Stunting di Wilayah Kerja Dinas Kesehatan Kota Medan Tahun 2020 - Fitriani Pramita Gurning; Rahmia Yunita Sari S; Rizky Widya Astuti; Ummu Balqis Munfaridah Sinambela (Jurnal Kesehatan, 2021)
Stunting or often called stunted or short is a condition of failure to thrive in children under five years of age (toddlers) due to chronic malnutrition and recurrent infections, especially during the first 1,000 days of life (HPK), from fetus to 23 month old child. Based on data from the Medan City Health Office, the stunting rate in Medan City was 491 with a percentage of 17.4% in 2019. Meanwhile, the stunting rate in Medan City in 2020 was 393 with a percentage of 0.71%. 491 cases of stunting under five, scattered in 25 districts and 104 villages. The highest case was in Medan Deli Subdistrict, with 101 cases and Titi Papan Village was a sub-district with the highest cases as many as 82 cases. The research design used in this study is descriptive research using a qualitative approach. The data collection technique in this study was carried out by means of observation. In the area of ​​Medan City, the STBM achievement is known to be 36.04% while the national target achievement is 68.06%. One of the factors causing the STBM achievement target not to be achieved is due to poor sanitation conditions that affect the health of children's growth and development which can lead to diarrhea, thus affecting children's nutrition.